2017
DOI: 10.1016/j.jhydrol.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological heterogeneity in agricultural riparian buffer strips

Abstract: Riparian buffer strips (RBS) may protect surface water and groundwater in agricultural settings, although their effectiveness, observed in field-scale studies, may not extend to a watershed scale. Hydrologically-controlled leaching plots have often shown RBS to be effective at buffering nutrients and pesticides, but uncontrolled field studies have sometimes suggested limited effectiveness. The limited RBS effectiveness may be explained by the spatiotemporal hydrological heterogeneity near non-irrigated fields.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…This is a crucial control on hydrological processes at the interface between the ground surface and soil, including the distribution of flowing water by overland flow and shallow underground flow. The continuity of overland flow or alternation with subsurface flow depends on the intensity of rainfall and the locations of relatively high infiltration patches isolated on hillslopes [69][70][71]. In this context, it is expected that high F/A catchments comprise a larger number of infiltration patches, and that subsurface flow dominates in these catchments.…”
Section: Discussionmentioning
confidence: 99%
“…This is a crucial control on hydrological processes at the interface between the ground surface and soil, including the distribution of flowing water by overland flow and shallow underground flow. The continuity of overland flow or alternation with subsurface flow depends on the intensity of rainfall and the locations of relatively high infiltration patches isolated on hillslopes [69][70][71]. In this context, it is expected that high F/A catchments comprise a larger number of infiltration patches, and that subsurface flow dominates in these catchments.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the Coverdale case, because bare areas were restricted to relatively insensitive parts of the catchment, there would be limited impacts on flood peaks by revegetating those zones. Instead, encouraging vegetation change towards rougher conditions in riparian zones, which is considered to be one of the best regions for management practices of surface water protection in catchments (Henault‐Ethier, Larocque, Perron, Wiseman, & Labrecque, ; Lyons, Trimble, & Paine, ), will yield greater benefits on reducing flood peaks from the catchment. This is because riparian zones are more efficient areas impacting overland flow delivery due to the converging shape of river catchments and the accompanying overland flow concentration (Gao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In riparian ecosystems, different riparian subzones may control the distribution of riparian plant species diversity. This may arise via differences in groundwater table, groundwater salinity, river discharge, and periodic flooding, among others [4,10,11]. We found that plant species diversity in riparian woodlands along the middle and lower reaches of the Yellow River in China varied with distance from the river.…”
Section: Variation In Plant Species Diversity Along Lateralmentioning
confidence: 84%
“…On one hand, this suggests that distance from the river may either have no significant impact on the distribution of species inhabiting the riparian zone, or that they have a significant influence on species composition alone [42]. On the other hand, there might be other environmental gradients [9,11,43] or anthropogenic disturbances [14,17,18] that control the characteristics of species evenness or diversity in this ecosystem that were not included in the present study.…”
Section: Variation In Plant Species Diversity Along Lateralmentioning
confidence: 89%
See 1 more Smart Citation